2020
DOI: 10.4317/jced.56855
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of sleep-related breathing disorders in children with malocclusion

Abstract: Background The paediatric population has a high incidence of sleep-related breathing disorders (SRBD). A notable risk factor is the presence of craniofacial abnormalities. The objective of the study was therefore to survey the prevalence of SRBD in patients presenting for interceptive treatment. Material and Methods Prospective study with a sample of 249 healthy patients. The “Paediatric Sleep Questionnaire” and “Sleep Disturbance Scale for Children” were completed by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 16 publications
0
12
0
1
Order By: Relevance
“…53 Other studies have found that the decreased palatal width is associated with a smaller dimension of the nasal upper airway, which may be a risk factor for reduced sleep quality. 2,33,60,63 Andersson and Sonnesen 32 have shown that decreased palatal width, snoring and restless sleep are more common in children with ADHD, which supports the hypothesis that dental occlusion and palatal dimension may have an impact on SDB symptoms and are associated with ADHD. 32,59 Orthodontic treatment with rapid maxillary expansion may improve the dimension of the nasal upper airway and thereby sleep quality due to, for example reducing nocturnal enuresis.…”
Section: Discussionmentioning
confidence: 66%
“…53 Other studies have found that the decreased palatal width is associated with a smaller dimension of the nasal upper airway, which may be a risk factor for reduced sleep quality. 2,33,60,63 Andersson and Sonnesen 32 have shown that decreased palatal width, snoring and restless sleep are more common in children with ADHD, which supports the hypothesis that dental occlusion and palatal dimension may have an impact on SDB symptoms and are associated with ADHD. 32,59 Orthodontic treatment with rapid maxillary expansion may improve the dimension of the nasal upper airway and thereby sleep quality due to, for example reducing nocturnal enuresis.…”
Section: Discussionmentioning
confidence: 66%
“…On the other hand, sleep-related breathing disorders in children with malocclusion have also be considered as another important casual factor for the development of a malocclusion, where patients with sleep-related breathing disorders (SRBD) had a smaller maxillary width ( p < 0.003), and according to the cephalometric study, less overbite ( p < 0.003) [ 66 ]. Furthermore, the prevalence of sleep-related breath disorders was higher among patients with a history of adenotonsillectomy ( p < 0.02) [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Typical nocturnal symptoms include mouth breathing, sweating, enuresis, sleep irregularities, shortness of breath and snoring, respiratory effort secondary to increased airway resistance, and pharyngeal obstruction. Daytime symptoms include rapid fatigue, hyperactivity, short temper, developmental and growth disability, mouth breathing, learning disability [1,23] . These symptoms, which vary in severity from primary snoring to obstructive sleep apnea (OSA), play a role in mediating the increased risks of cardiometabolic or neuropsychiatric disorders in preterm infants and adults [24] .…”
Section: Signs and Symptomsmentioning
confidence: 99%
“…A variety of psychological and neuropsychiatric studies have clearly linked it to learning and attention deficits and behavioral problems [27] . Craniofacial development is influenced by genetic and functional factors, meanwhile, mouth breathing causes increased nasal breathing resistance, altering muscle balance and affecting the child's craniofacial development, thus increasing the risk of malocclusion [23] . Respiratory disorders not only cause impairment in affected children, but also lead parents to a relevant reduction in quality of life [28] .…”
Section: Signs and Symptomsmentioning
confidence: 99%